Halo nevus without halo. - Milano, A.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2014)
Case report. A 9 year old boy was first observed because the mother has noticed significant changes of two acquired melanocytic nevi, one on the back and the other on the right hand. The family and personal history was negative for risk of melanoma. The nevus of the hand arose from two months and was progressively growing; the physical examination and dermoscopy confirmed the clinical diagnosis of Reed nevus. The palpable nevus of the back (Fig. 1) showed on careful observation a reddish tinge and dermoscopic examination showed a central depletion in the number of globules that had also blurred margins (Fig. 3). In the subsequent observations after 3 (Fig. 2, 4), 11 (Fig. 5, 7) and 15 months (Fig. 6, 8) the pigmented nevus became less noticeable until it completely disappeared leading us to diagnose regressing nevus. Meanwhile the Reed nevus stopped growing. Moreover, a typical halo nevus appeared on one leg. The appearance of the latter nevus led us to consider the nevus of the back as a halo nevus without halo.